Structural, morphological, and functional diversity of amyloid oligomers. Issue 19 (17th July 2015) - Breydo, Leonid; Uversky, Vladimir N.
Abstract : Protein misfolding and aggregation are known to play a crucial role in a number of important human diseases (Alzheimer's, Parkinson's, prion, diabetes, cataracts, etc.) as well as in a multitude of physiological processes. Protein aggregation is a highly complex process resulting in a variety of aggregates with different structures and morphologies. Oligomeric protein aggregates (amyloid oligomers) are formed as both intermediates and final products of the aggregation process. They are believed to play an important role in many protein aggregation‐related diseases, and many of them are highly cytotoxic. Due to their instability and structural heterogeneity, information about structure, mechanism of formation, and physiological effects of amyloid oligomers is sparse. This review attempts to summarize the existing information on the major properties of amyloid oligomers.